2020
DOI: 10.1016/j.celrep.2020.108223
|View full text |Cite
|
Sign up to set email alerts
|

The Lipid Handling Capacity of Subcutaneous Fat Is Programmed by mTORC2 during Development

Abstract: SUMMARY Overweight and obesity are associated with type 2 diabetes, non-alcoholic fatty liver disease, cardiovascular disease and cancer, but all fat is not equal, as storing excess lipid in subcutaneous white adipose tissue (SWAT) is more metabolically favorable than in visceral fat. Here, we uncover a critical role for mTORC2 in setting SWAT lipid handling capacity. We find that subcutaneous white preadipocytes differentiating without the essential mTORC2 subunit Rictor upre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 96 publications
(128 reference statements)
3
10
0
Order By: Relevance
“…Indeed, leptin and species of free fatty acids have been identified as potential sensory stimuli acting in WAT [15, 16]. Our data provide additional evidence for this hypothesis since arborization of sensory neurons is lost upon ablation of adipose mTORC2, a critical regulator of energy uptake and storage in WAT [23, 25]. In addition, the observed reduction of sensory innervation in WAT lacking mTORC2 coincides with hyperinsulinemia and insulin resistance.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Indeed, leptin and species of free fatty acids have been identified as potential sensory stimuli acting in WAT [15, 16]. Our data provide additional evidence for this hypothesis since arborization of sensory neurons is lost upon ablation of adipose mTORC2, a critical regulator of energy uptake and storage in WAT [23, 25]. In addition, the observed reduction of sensory innervation in WAT lacking mTORC2 coincides with hyperinsulinemia and insulin resistance.…”
Section: Discussionsupporting
confidence: 60%
“…It is composed of four core components including the kinase subunit mTOR and the mTORC2-specific subunit rapamycin-insensitive companion of mTOR (RICTOR) [17][18][19]. Studies of adipose-specific Rictor knockout mice revealed that loss of adipose mTORC2 causes reduced glucose uptake and impaired lipid handling in adipocytes [20][21][22][23][24][25]. Furthermore, loss of adipose mTORC2 non-cell-autonomously causes hyperinsulinemia and systemic insulin resistance [20,21,23].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Bacteroidetes , Firmicutes in phylum and Parasutterell and Canaidatus_Saccharimonas in genus level showed high correlation with iWAT and BAT weight and metabolites contents correlated with TCA cycle. Fat in scWAT is more easily metabolized than visceral WAT, which including eWAT and the adipose tissue around liver and heart ( 40 ). Compared with visceral WAT, scWAT is more likely to be mobilized, browned, hydrolyzed, oxidized and thermogenerated ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that sensory neurons may directly communicate the metabolic state of WAT to CNS [ [13] , [14] , [15] ]. Our data provide evidence that this communication is disrupted upon ablation of adipose mTORC2, a critical regulator of energy uptake and storage in WAT [ 23 , 25 ]. We found that reduction of sensory innervation in WAT coincides with systemic insulin resistance.…”
Section: Discussionmentioning
confidence: 95%
“…It is composed of four core components including the kinase subunit mTOR and the mTORC2-specific subunit rapamycin-insensitive companion of mTOR (RICTOR) [ [16] , [17] , [18] , [19] ]. Studies in adipose-specific Rictor knockout mice revealed that loss of adipose mTORC2 causes reduced glucose uptake and impaired lipid handling in adipocytes [ [20] , [21] , [22] , [23] , [24] , [25] ]. Furthermore, loss of adipose mTORC2 non-cell-autonomously causes hyperinsulinemia and systemic insulin resistance [ 20 , 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%